2023
DOI: 10.1029/2022ms003270
|View full text |Cite
|
Sign up to set email alerts
|

An Intercomparison of Large‐Eddy Simulations of a Convection Cloud Chamber Using Haze‐Capable Bin and Lagrangian Cloud Microphysics Schemes

Abstract: Recent in situ observations show that haze particles exist in a convection cloud chamber. The microphysics schemes previously used for large‐eddy simulations of the cloud chamber could not fully resolve haze particles and the associated processes, including their activation and deactivation. Specifically, cloud droplet activation was modeled based on Twomey‐type parameterizations, wherein cloud droplets were formed when a critical supersaturation for the available cloud condensation nuclei (CCN) was exceeded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Although Morrison et al (2018) have shown the artificially enhanced broadening of DSDs associated with vertical diffusion in a Eulerian dynamical model, Yang et al (2022) find that the impact of numerical broadening of the DSDs in the cloud-chamber LES is very small due to the relatively fine grid spacing, short time step, and weak vertical velocity compared to convection in an atmospheric boundary layer. Additionally, Yang et al (2023) shows that the cloud-chamber LES results from an Eulerian bin microphysics scheme agree well with those from a Lagrangian microphysics scheme, and the latter does not experience numerical diffusion. To narrow the scope of this study, we will focus on the sensitivity of the results to the chamber configurations rather than numerical methods.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Although Morrison et al (2018) have shown the artificially enhanced broadening of DSDs associated with vertical diffusion in a Eulerian dynamical model, Yang et al (2022) find that the impact of numerical broadening of the DSDs in the cloud-chamber LES is very small due to the relatively fine grid spacing, short time step, and weak vertical velocity compared to convection in an atmospheric boundary layer. Additionally, Yang et al (2023) shows that the cloud-chamber LES results from an Eulerian bin microphysics scheme agree well with those from a Lagrangian microphysics scheme, and the latter does not experience numerical diffusion. To narrow the scope of this study, we will focus on the sensitivity of the results to the chamber configurations rather than numerical methods.…”
Section: Introductionmentioning
confidence: 66%
“…Additionally, Yang et al. (2023) shows that the cloud‐chamber LES results from an Eulerian bin microphysics scheme agree well with those from a Lagrangian microphysics scheme, and the latter does not experience numerical diffusion. To narrow the scope of this study, we will focus on the sensitivity of the results to the chamber configurations rather than numerical methods.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The LES of the Pi Chamber is a modified version of the System for Atmospheric Modeling (SAM) (Khairoutdinov & Randall, 2003;Thomas et al, 2019;Yang et al, 2022Yang et al, , 2023, with a grid spacing of 3.125 cm in each dimension. This small grid spacing is several orders of magnitude smaller than cloud-scale LES, resolving fluctuations in environmental properties at very small scales.…”
Section: Les Of Pi Chambermentioning
confidence: 99%
“…Other representations of cloud microphysics, such as Lagrangian super‐droplet method, do not represent non‐activated aerosol particles and cloud droplets as separate classes (Grabowski, 2020a; Hoffmann et al., 2019) which may cause the super‐droplet method to be a better representation of CCN activation than bin microphysics. However, both the super‐droplet method and bin microphysics approach produce slightly different but comparable cloud droplet spectra (Grabowski, 2020a, 2020b; Xue et al., 2022; Yang et al., 2023).…”
Section: Introductionmentioning
confidence: 99%